Rank 2 Nichols Algebras of Diagonal Type over Fields of Positive Characteristic - Wang, J.; Heckenberger, I. (Symmetry, Integrability and Geometry: Methods and Applications, 2015)
The paper introduces a new method to determine all rank two Nichols algebras of diagonal type over fields of positive characteristic.